MENINGKATKAN KETERAMPILAN MENULIS PUISI MELALUI PENDEKATAN PEMBELAJARAN KONTEKSTUAL PADA SISWA KELAS III SEKOLAH DASAR - Purba, Putry Sauhur; Girsang, Mei Lyna (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2019)
This study aims to improve the learning outcomes of class III B students at SD Negeri 066652 Bakti Luhur, Medan in the material of writing poetry through a contextual learning approach. This research is Kemmis and Mc Class Action Research (CAR). Taggart Research Subjects were students of class III B, totaling 20 students. Data collection techniques to see the implementation of contextual learning using tests, research instruments using test sheets and observation sheets. Data analysis techniques used descriptive quantitative and qualitative descriptive.The results of the study showed that the application of the contextual learning approach in Indonesian language learning could improve student learning outcomes in the poetry writing material of class III B SD Negeri 066652 Bakti Luhur. This is evidenced by the increase in student learning outcomes in class III B from cycle I to cycle II. Student learning outcomes in the first cycle with an average of 60.29 and the second cycle 90.29. The level of completeness in the first cycle is 10% and in the second cycle becomes 90%.